2015
DOI: 10.1021/acs.inorgchem.5b00689
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioStudy of the Adsorption of Small Molecules on Metal–Organic Frameworks with Oxo-centered Trimetallic Building Units: The Role of the Undercoordinated Metal Ion

Abstract: The interactions of H2, CO, CO2, and H2O with the undercoordinated metal centers of the trimetallic oxo-centered M3(III)(μ3-O)(X) (COO)6 moiety are studied by means of wave function and density functional theory. This trimetallic oxo-centered cluster is a common building unit in several metal-organic frameworks (MOFs) such as MIL-100, MIL-101, and MIL-127 (also referred to as soc-MOF). A combinatorial computational screening is performed for a large variety of trimetallic oxo-centered units M3(III)O (M = Al(3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 90 publications
(156 reference statements)
2
41
0
Order By: Relevance
“…We have previously employed the PBE/6-311++G** combination in studies of the Kubas binding of H 2 to early first row transition metals. 26 Recent benchmarking work has shown that generalized gradient approximation functionals, in conjunction with the D3 dispersion corrections, perform similarly to high level ab initio methods (CCSD(T)) for H 2 binding to organic substrates decorated with metal atoms, 35 transition metal oxide clusters, 36 metal organic framework building units including transition metals, 37 and graphene decorated with transition metals. 38 All calculations were performed in the Gaussian 09 code, revision D.01.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously employed the PBE/6-311++G** combination in studies of the Kubas binding of H 2 to early first row transition metals. 26 Recent benchmarking work has shown that generalized gradient approximation functionals, in conjunction with the D3 dispersion corrections, perform similarly to high level ab initio methods (CCSD(T)) for H 2 binding to organic substrates decorated with metal atoms, 35 transition metal oxide clusters, 36 metal organic framework building units including transition metals, 37 and graphene decorated with transition metals. 38 All calculations were performed in the Gaussian 09 code, revision D.01.…”
Section: Resultsmentioning
confidence: 99%
“…9). The DFT-D3 approach (hybrid functional PBE0-D3, cc-pVTZ-PP basis set for Cu, def2-TZVPP for the interacting H 2 and def2-TZVP for all other atoms) has been validated against coupled cluster theory including single, double and partially triple excitations (CCSD(T)) calculations (Supplementary Table 6), and has also been used elsewhere719. Two open Cu(I) metal centres per formula unit are statistically distributed in Cu(I)-MFU-4 l 13.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been shown by others 38,39 to provide reasonable geometry, IR and electronic data in benchmarking against ab initio techniques. [40][41][42][43] Both Gaussian 09 revision D.01 44 and Gaussian 16 revision A.03 45 have been used to perform the calculations presented herein;…”
Section: Methodsmentioning
confidence: 99%